2017
DOI: 10.1513/annalsats.201606-469oc
|View full text |Cite
|
Sign up to set email alerts
|

Residence in Rural Areas of the United States and Lung Cancer Mortality. Disease Incidence, Treatment Disparities, and Stage-Specific Survival

Abstract: Higher rural smoking rates drive increased disease incidence and per capita lung cancer mortality in rural areas of the United States. There were no rural-urban discrepancies in diagnostic stage, suggesting similar access to diagnostic services. Rural patients diagnosed with stage I non-small cell lung cancer had shorter survival, which may reflect disparities in access to surgical care. No survival difference for patients with advanced-stage lung cancer is attributed to lack of effective treatment during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
122
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 25 publications
7
122
3
Order By: Relevance
“…Similar to our findings, a recent study using national SEER‐Medicare data demonstrated no relationship between rurality and stage at diagnosis . In contrast, others have reported more advanced‐stage disease in rural patients presenting with lung cancer .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to our findings, a recent study using national SEER‐Medicare data demonstrated no relationship between rurality and stage at diagnosis . In contrast, others have reported more advanced‐stage disease in rural patients presenting with lung cancer .…”
Section: Discussionsupporting
confidence: 90%
“…Lung cancer is the leading cause of cancer death in the United States among men and women . In rural areas, lung cancer mortality is up to 20% higher than in metropolitan areas . Maine, the most rural state, has the 5th highest lung cancer incidence in the United States and the highest in New England .…”
mentioning
confidence: 99%
See 3 more Smart Citations